Commissioners of Audit: Reports to the Board - Great Britain. Exchequer and Audit Department; Australian Joint Copying Project; National Library of Australia; Library of New South Wales; Great Britain. Public Record Office (Canberra : Australian Joint Copying Project, 1789)
Reports to the Commissioners of Audit from the staff of the Audit Office concerning inspection of accounts, and queries of accounts from governors, heads of convict services in the colonies and the Emigration Commissioners
National Library of Australia holds microfilm master.
Filmed as part of the Australian Joint Copying Project by the National Library of Australia and the Library of New South Wales.
Selected extracts from pieces have been filmed.
Australian Joint Copying Project handbook. Part 6 : Board of Trade; Treasury; Exchequer and Audit Department; Privy Council; Board of Longitude - class and piece list
Public Record Office AO 10/5-93.
Also available online
Keywords: Great Britain. -- Exchequer and Audit Department -- Records and correspondence; Great Britain -- Colonial Land and Emigration Commission -- Auditing; Convicts -- Great Britain -- Colonies; Great Britain -- Colonies -- Appropriations and expenditures